2008
DOI: 10.1097/id.0b013e318166d800
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Field Effect on Peri-Implant Osteogenesis: A Histologic and Histomorphometric Study

Abstract: The use of a device generating a positive/negative electrical field resulted in the presence of woven bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…A growing number of studies have demonstrated that external electric fields and applied currents could induce oste ogenesis, promote the consolidation of fracture callus and accelerate skeletal attachment. [17][18][19][20][21] Especially in orthopedics, electric stimulation devices have been used to promote healing of bony nonunion. [22,23] These studies strongly suggest the pre dominant role of the physiologically relevant electrical signals in directing wound healing.…”
mentioning
confidence: 99%
“…A growing number of studies have demonstrated that external electric fields and applied currents could induce oste ogenesis, promote the consolidation of fracture callus and accelerate skeletal attachment. [17][18][19][20][21] Especially in orthopedics, electric stimulation devices have been used to promote healing of bony nonunion. [22,23] These studies strongly suggest the pre dominant role of the physiologically relevant electrical signals in directing wound healing.…”
mentioning
confidence: 99%
“…Although many attempts, such as hyperbaric oxygenation, electrical stimulation, low‐intensity pulsed ultrasound stimulation, and growth factors, have been made to accelerate bone formation, these approaches are associated with technical difficulties, speculative efficacy, and controversial safety profile . Fortunately, recent advances in regenerative medicine have enabled stem cell therapy to be a promising strategy to shorten the consolidation period and decrease potential complications in DO .…”
mentioning
confidence: 99%
“…Various materials were examined for treating implants, including resorbed polymers (e.g., chitozan) in combination with proteins (BMP), which facilitated the cells’ interactions with the substrate (Minamide et al, 2005; Lopez-Lacomba et al, 2006; Middleton et al, 2007); polyglactin mesh with growing fibroblasts (Sparks et al, 2007); positively-charged phosphorylcholine, which that is beneficial for cells and, therefore, improves the biocompatibility of medical devices with tissue in the organism (Susin et al, 2008); and RGD peptides (Secchi et al, 2007). We applied extracellular proteins (collagen and fibrin) for the preliminary treatment of titanium implants, which was more adequate for the organism and, consequently, more effective for the migration of cells from tissue than chemical, physical, or polymer treatments (Cho, Jung, 2003; Reclaru et al, 2003; Serro and Saramago, 2003; Stentport and Johansson, 2003; Fujibayashi et al, 2004; Park et al, 2007; Shibli et al, 2007; Giannunzio et al, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Along with the application of various biological materials for improving the implant surface, studies were undertaken to evaluate physical factors that may facilitate the regeneration of bone tissue, e.g., various sterilization methods (Serro and Saramago, 2003), laser-treatment (Cho and Jung, 2003), electrical stimulation (Giannunzio et al, 2008), and titanium oxidation (Shibli et al, 2006).…”
mentioning
confidence: 99%